2009
DOI: 10.1109/tnsre.2009.2023298
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Neural Recording With Single Low-Power Integrated Circuit

Abstract: We present benchtop and in vivo experimental results from an integrated circuit designed for wireless implantable neural recording applications. The chip, which was fabricated in a commercially available 0.6-μm 2P3M BiCMOS process, contains 100 amplifiers, a 10-bit analog-to-digital converter (ADC), 100 threshold-based spike detectors, and a 902–928 MHz frequency-shift-keying (FSK) transmitter. Neural signals from a selected amplifier are sampled by the ADC at 15.7 kSps and telemetered over the FSK wireless da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(112 citation statements)
references
References 15 publications
0
110
0
2
Order By: Relevance
“…There has been considerable effort devoted to developing technology for interfacing with the central nervous system in laboratory animals and humans [1-2]. Even though these efforts have led to marvelous technological advancements in circuits and systems, some of the resulting devices may find little use in their application domain, because the specifics of the targeted applications or the realistic needs of the end users may not be taken into account.…”
mentioning
confidence: 99%
“…There has been considerable effort devoted to developing technology for interfacing with the central nervous system in laboratory animals and humans [1-2]. Even though these efforts have led to marvelous technological advancements in circuits and systems, some of the resulting devices may find little use in their application domain, because the specifics of the targeted applications or the realistic needs of the end users may not be taken into account.…”
mentioning
confidence: 99%
“…The use of mobility of network components is considered to be a prospective balancing method. In various studies [3], [13], authors have shown that the use of mobility is good for increasing the autonomous actions of a sensor network. THE WIRELESS SENSOR NETWORK The primary task of the network reconfiguration method is to increase the time interval of the network topology change.…”
Section: Related Researchmentioning
confidence: 99%
“…Currently, researchers are working to improve the chronic recording quality for these implanted sensors and also to develop fullyimplantable wireless systems. [168][169][170] Implanted systems will reduce the risk of infection as well as noise that can contaminate the signal as it is communicated via transcutaneous wires. Transcutaneous wires are susceptible to breakage and this risk could be eliminated by a fully implantable system.…”
Section: Ecog and Intracortical Microelectrode Bcismentioning
confidence: 99%